Development and establishment of a high frequency monitoring system of the agri-food sector of Guatemala/ Construcción y establecimiento de un sistema de monitoreo de alta frecuencia del sector agroalimentario de Guatemala - Manners, Rhys; Jimenez, Daniel Ricardo; Martínez, Jesús David; Borrayo, Andrea Surama; Bonilla, Melissa; Ramos Solorzano, Gresia Dalal; Muller, Anna (2023)
The report details the creation and implementation of the SiMASAG (High-Frequency Monitoring System for the Agrifood Sector) in Guatemala, designed to analyze and visualize seasonal dietary variations among Guatemalans and their connections with socio-environmental factors. Key to SiMASAG's development is MeMO, an automated system for data collection and processing. MeMO utilizes cellphone and WhatsApp surveys, continuously refined for enhanced efficacy in data gathering and processing. Emphasizing a human-centered design, the project has optimized survey methodologies to effectively engage participants, enabling precise user profiling for the surveys processed by MeMO. This document also highlights SiMASAG's initial findings on dietary trends in three Chiquimula Department municipalities. It outlines future plans to augment the system, incorporating additional critical data like market trends, food supply chains, and climatic conditions.